Innovatív pénzügyi termékek és szolgáltatások diffúziója - Kovácsné Kovács, Andrea (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
The thesis aims to explore the effects of current phenomena - globalisation, liberalisa-tion and innovation - on the financial world. No analysis can fail to consider today's eco-nomic crisis, which is often seen as the consequence of liberalisation and the lack of trans-parency of innovative financial products. According to leading economists the financial system need to be controlled. Other analysts say that the financial system is already over-regulated compared to other areas. Some analysts say that the market of financial innova-tions must be downsized as recent years have proved that mistakes in the market are much more dangerous than previously thought and consequently financial innovation -at least in the short term - has no future. Others disagree pointing out the economic prosperity, which is the result of financial innovation. My thesis outlines these theories and I am planning to carry out empirical studies in order to decide which of these theories to reject and which of them to accept.